Pengaruh Penggunaan Ekstrak Daun Jeruju (Acanthus Ilicifolius) Dengan Dosis Berbeda Terhadap Gambaran Darah, Gejala Klinis Dan Kelulushidupan Lele Dumbo (Clarias gariepinus) Yang Diinfeksi Aeromonas hydrophila - Ziyadaturrohmah, Siti; Prayitno, Slamet Budi; Sarjito, Sarjito; Hidayati, Nurul; Saptiani, Gina (Journal of Aquaculture Management and Technology, 2013)
Aeromonas hydrophila is a causative agent of Haemoragic Septicemia on Clarias gariepinus. The aim of this research was to investigate the effect of Acanthus ilicifolius leaf extract toward survival rate of C. gariepinus infected by A. hydrophila. Tested fish C. gariepinus 10-12 cm and weight Â±25 gr. This reasearch was conducted by 4(four) treatments namely, A (treatment with no leaf ectract A. ilicifolius), B (300 ppm), C (500 ppm), and D (700) 30 minutes immersion. The challenge test was done by injecting 0,1 mL A. hydrophila suspensions with dosage 108 cell/mm3 intra-muscular by experiment fishes. Observation was performed for 5 days after infection such as blood profile, clinical symptoms, and survival rate of C. gariepinus. The results of blood profile after the infection showed that hematokrit of A, B, C, and D treatments was 17,33%, 14,67%, 15,00%, 19,67% respectively. Percentage of the highest erythrocyte was at D treatment 1,79x106 sel/mm3, B 1,72 x106 sel/mm3, A 1,64x106 sel/mm3, C 1,52x106 sel/mm3. Percentage of the highest leuchocyte was at C treatment 5,43x104 sel/mm3, D 3,11x104 sel/mm3, B 2,63x104 sel/mm3, and A 2,32x104 sel/mm3. The result showed that clinical symptoms of A. hydrophila infected fish swam abnormally, injured and haemoragic on the skin along with damaged on the body. Immersion with A. ilicifolius extract leaf past infection indicated that they were not significantly different on C. gariepinus survival rate. Therefore the dosage of A. ilicifolius leaf extract did not sufficient to protect C. gariepinus from A. hydrophila infection.